Pengenalan Literasi Keuangan dan Pengendalian Personal Financial Planning untuk Generasi Z - Sakinah, Nur; Martha Darman, Dian; Arfah, Lita; Marro'aini, Marro'aini; Jonkenedi, Jonkenedi (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
Consumerist behavior that has become a habit of society has resulted in a tendency to reduce cultural development. There are still many people who do not realize the importance of having a view on financial management in their personal lives because of the assumption that personal financial planning is only for high-income people and financial planning is only carried out by an organization or company. The aim of carrying out community service for Al-Izhar IT Vocational School students in Pekanbaru is to participate in raising awareness among these students through the introduction of financial literacy, so that generation Z understands and recognizes financial literacy and personal financial planning to prepare for a better future as early as possible. The implementation method was designed and implemented using the PAR (Participatory Action Research) method, which involves researchers and participants in collaboration to encourage active participation, feedback, and joint knowledge creation. The results achieved were that students understood the concept of financial literacy, were able to avoid behavior that could influence generation Z's financial decisions, and had self-control in personal financial planning.